Long-term outcomes for epidemic viral pneumonia survivors after discharge from the intensive care unit: a systematic review - Larrie Rabelo Laporte; Alexandre von Flach Garcia Chavez; Otavio Tavares Ranzani; Juliana Caldas; Rogerio da Hora Passos; João Gabriel Rosa Ramos (Einstein (São Paulo), 2024)
ABSTRACT Objective To review the long-term outcomes (functional status and psychological sequelae) of survivors of critical illnesses due to epidemic viral pneumonia before the COVID-19 pandemic and to establish a benchmark for comparison of the COVID-19 long-term outcomes. Methods This systematic review of clinical studies reported the long-term outcomes in adults admitted to intensive care units who were diagnosed with viral epidemic pneumonia. An electronic search was performed using databases: MEDLINE®, Web of Science™, LILACS/IBECS, and EMBASE. Additionally, complementary searches were conducted on the reference lists of eligible studies. The quality of the studies was assessed using the Newcastle-Ottawa Scale. The results were grouped into tables and textual descriptions. Results The final analysis included 15 studies from a total of 243 studies. This review included 771 patients with Influenza A, Middle East Respiratory Syndrome, and Severe Acute Respiratory Syndrome. It analyzed the quality of life, functionality, lung function, mortality, rate of return to work, rehospitalization, and psychiatric symptoms. The follow-up periods ranged from 1 to 144 months. We found that the quality of life, functional capacity, and pulmonary function were below expected standards. Conclusion This review revealed great heterogeneity between studies attributed to different scales, follow-up time points, and methodologies. However, this systematic review identified negative long-term effects on patient outcomes. Given the possibility of future pandemics, it is essential to identify the long-term effects of viral pneumonia outbreaks. This review was not funded. Prospero database registration: (www.crd.york.ac.uk/prospero) under registration ID CRD42021190296.